2010
DOI: 10.1186/1476-511x-9-88
|View full text |Cite
|
Sign up to set email alerts
|

Studies on antidyslipidemic effects of Morinda citrifolia (Noni) fruit, leaves and root extracts

Abstract: BackgroundThe objective of present study was to provide the pharmacological basis for the medicinal use of Morinda citrifolia Linn in dyslipidemia using the aqueous-ethanolic extracts of its fruits (Mc.Cr.F), leaves (Mc.Cr.L) and roots (Mc.Cr.R).ResultsMc.Cr.F, Mc.Cr.L and Mc.Cr.R showed antidyslipidemic effects in both triton (WR-1339) and high fat diet-induced dyslipidemic rat models to variable extents. All three extracts caused reduction in total cholesterol and triglyceride levels in triton-induced dyslip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 26 publications
1
38
1
2
Order By: Relevance
“…[20][21][22][23][24][25] very low density lipoprotein (VLDL) and low density lipoprotein (LDL) were calculated according to following formulas 26 :…”
Section: Biochemical Analysis Of Plasmamentioning
confidence: 99%
“…[20][21][22][23][24][25] very low density lipoprotein (VLDL) and low density lipoprotein (LDL) were calculated according to following formulas 26 :…”
Section: Biochemical Analysis Of Plasmamentioning
confidence: 99%
“…As for the study by Mandukhail et al (2010), the benefits found were for the pulp, the leaves, and the aqueous extract of the fruit. In the present study, higher serum levels of total cholesterol and LDL were identified in the group that ingested whole fruit infusion, and may indicate that some part of the noni may have some component responsible for such increase.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al (2012) found that supplementation with fermented noni juice promoted lower serum level of total cholesterol and triglyceride in hamsters fed a high fat diet. In turn, Mandukhail et al (2010) demonstrated that different parts of the fruit (pulp, leaves and aqueous extract) promoted an improvement in the lipid profile in rats fed a high-fat diet, attributing such effect to the inhibition, biosynthesis, secretion and absorption of lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of noni for human consumption has become very controversial in recent years, since on the one hand several authors (Kadiri et al, 1999;Collins, 2009;Serafini et al, 2011;Alencar et al, 2013) have conducted experiments in vivo use of this fruit and have reported a nephrotoxic and genotoxic effect, other authors have evaluated the pharmacological activity of M. citrifolia by in vivo and clinical trials and found among other anti cancer effect (Kamiya et al, 2010) agent hepatoprotective (Lin et al, 2013), anti dyslipidemia (Mandukhail et al, 2010), immune stimulator (Krishnaiah et al, 2012), anthelminthic activity (Brito et al, 2009) and anti inflammatory (Fletcher et al, (2013). Given these contradictory highlighted in some countries have banned its use, while the vast majority is still used for the treatment of various diseases.…”
Section: Introductionmentioning
confidence: 99%